Impacto de la aplicación NIC 1 y NEC en la elaboración de estados financieros de la Cooperativa De Ahorro Y Crédito Huaquillas LTDA. En el 2019. - Novillo Castro, Manuel Octavio (My University, 2021)
This study addresses the issue of the preparation and treatment of financial information in savings and credit cooperatives; The incidence of the International Accounting Standards (IAS) and the Accounting Standards of Ecuador (NEC) is characterized, under the context of performance, liquidity and administrative management when comparing accounting balances. The relevance lies in the fact that the impact of the IAS and NEC on the financial statements of financial entities is unknown, what are their facilities, benefits or disadvantages from a practical perspective when evaluating their performance through economic indicators; The objective is to analyze the impact of the application of IAS 1 and NEC in the preparation of the financial statements of the Huaquillas Savings and Credit cooperative through a descriptive investigation to improve the accounting / tax situation of the company. The type of study is descriptive, starting from the pragmatic paradigm combining both theoretical and practical criteria of the application of the NIC / NEC in the social reality of the Cooperativa de Ahorro y Crédito Huaquillas; abductive analysis is used to compare information in the same context and systematic analysis to determine how it affects accounting / tax management. The main results show that the impact of the IAS is mostly positive, it favors the treatment of financial information, facilitates the justification of exemptions and deductions, improves transparency for both external and internal users of information, and promotes the entry of new markets by standardizing the criteria for interpreting your financial situation. It is recommended to design a macro plan to accelerate the adoption of international standards in the national territory; so that the phases for its application are standardized, improving the transparency of accounting information in the public and private sectors, facilitating development and financial inclusion.
El presente estudio aborda la temática de la elaboración y tratamiento de la información financiera en la Cooperativa de ahorro y crédito Huaquillas Ltda.; la cual caracteriza la incidencia de las Normas Internacionales de Contabilidad (NIC) y Normas Ecuatorianas de Contabilidad (NEC), bajo el contexto del rendimiento, liquidez y gestión administrativa al comparar los balances contables. La relevancia radica en que se desconoce el impacto de las NIC y NEC sobre los estados financieros de las entidades financieras, cuáles son sus facilidades, prestaciones o desventajas desde la perspectiva práctica al evaluar su desempeño a través de indicadores económicos; el objetivo es Analizar el impacto de la aplicación de las NIC 1 y NEC en la elaboración de los estados financieros de la cooperativa de Ahorro y Crédito Huaquillas mediante una investigación descriptiva para mejorar la situación contable/tributaria de la empresa. El tipo de estudio es descriptivo, partiendo del paradigma pragmático al conjugar criterios tanto teóricos como prácticos de la aplicación de las NIC/NEC en la realidad social de la Cooperativa de Ahorro y Crédito Huaquillas; se utiliza el análisis abductivo para comparar información bajo el mismo contexto y análisis sistemático para determinar el grado de afectación a la gestión contable/tributaria. Los principales resultados evidencian que el impacto de las NIC es mayormente positivo, favorece el tratamiento de la información financiera, facilita justificar las exenciones y deducciones, mejora la transparencia para los usuarios de la información tanto externos como internos y potencia el ingreso a nuevos mercados al estandarizar los criterios para interpretar su situación financiera. Se recomienda diseñar un plan macro para acelerar la adopción de las normas internacionales en el territorio nacional; de modo que se estandarice las fases para su aplicación mejorando la transparencia de la información contable en el sector público y privado, facilitando el desarrollo e inclusión financiera.
Keywords: NORMAS INTERNACIONALES DE CONTABILIDAD; ESTADOS FINANCIEROS; COOPERATIVA DE AHORRO Y CRÉDITO